Can gingival crevicular blood effectively screen for diabetes in Chinese patients with moderate to severe periodontitis? A pilot study - Juan Wu; Liangyuan Lin; Rui Zhang; Shuai Liu; Weibin Sun (Elsevier, 2021)
Background/purpose: The early diagnosis of diabetes is essential for the prevention of complications. Periodontitis has been identified as the sixth complication of diabetes and chair-side screening may improve diagnosis of diabetes. This study evaluated whether gingival crevicular blood (GCB) available during routine periodontal examination can be used to screen for diabetes in Chinese patients with moderate to severe periodontitis. Materials and methods: Finger-stick blood (FSB) and GCB were collected from patients (18 with diabetes and 42 without diabetes) during routine periodontal probing and analyzed for glucose and hemoglobin A1c (HbA1c) levels. Results: In the diabetic group, the mean glucose levels in GCB and FSB were 12.21 ± 3.86 and 12.61 ± 4.19 mmol/L respectively, while those of the non-diabetic group were 6.14 ± 0.85 and 6.15 ± 0.87 mmol/L, respectively. The average HbA1c values of the diabetic group were 7.72% ± 1.71% and 7.89% ± 1.78% in GCB and FSB, respectively, while those of the non-diabetic group were 5.28% ± 0.31% and 5.23% ± 0.32%, respectively. Highly significant correlations were found between GCB and FSB glucose levels (r = 0.993 for the diabetic group, and r = 0.977 for the non-diabetic group) and between GCB and FSB HbA1c levels (r = 0.977 for the diabetic group, and r = 0.829 for the non-diabetic group). Conclusion: Our study results indicate that GCB available during routine periodontal examination may be acceptable for the analyses of blood glucose and HbA1c levels. The approach is suitable for screening undiagnosed diabetes in a dental setting.